3.9k views
4 votes
Find (fxf)(0)

F(x)+3x-2

2 Answers

1 vote

Final answer:

To find (fxf)(0), substitute 0 into the given function f(x) = x + 3x - 2. The resulting value is -2.

Step-by-step explanation:

To find (fxf)(0), we need to substitute 0 into the given function. The function is f(x) = x + 3x - 2. Substituting 0 for x, we get f(0) = 0 + 3(0) - 2 = -2. Therefore, (fxf)(0) = f(f(0)) = f(-2).

User Sthe
by
6.6k points
4 votes
Given that the function is f(x)=3x-2, then the value of f(0) will be given by:
f(0)=3(0)-2
simplifying the above we get:
f(0)=0-2
f(0)=-2
the answer is f(0)=-2, in other words, when x=0, then y=-2
User Kelcey
by
6.0k points